Improved repair of chondral and osteochondral defects in the ovine trochlea compared with the medial condyle. Issue 11 (27th June 2013) - Orth, Patrick; Meyer, Heinz‐Lothar; Goebel, Lars; Eldracher, Mona; Ong, Mei Fang; Cucchiarini, Magali; Madry, Henning
Abstract: Associations between topographic location and articular cartilage repair in preclinical animal models are unknown. Based on clinical investigations, we hypothesized that lesions in the ovine femoral condyle repair better than in the trochlea. Full‐thickness chondral and osteochondral defects were simultaneously established in the weightbearing area of the medial femoral condyle and the lateral trochlear facet in sheep, with chondral defects subjected to subchondral drilling. After 6 months in vivo, cartilage repair and osteoarthritis development was evaluated by macroscopic, histological, immunohistochemical, and biochemical analyses. Macroscopic and histological articular cartilage repair and type‐II collagen immunoreactivity were better in the femoral trochlea, regardless of the defect type. Location‐independently, osteochondral defects induced more osteoarthritic degeneration of the adjacent cartilage than drilled chondral lesions. DNA and proteoglycan contents of chondral defects were higher in the condyle, reflecting physiological topographical differences. The results indicate that topographic location dictates the structural patterns and biochemical composition of the repair tissue in sheep. These findings suggest that repair of cartilage defects at different anatomical sites of the ovine stifle joint needs to be assessed independently and that the sheep trochlea exhibits cartilage repair patterns reflective of the human medial femoral condyle. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1772–1779, 2013